Answer:
x=11
Step-by-step explanation:
Please see attached image.
Number 19
price :$16
pay :10%
ask:each monthly payment
answer:
pay =10%×$160=$16
each monthly payment
={$160-$16}÷6
144÷6
$24
number 20
weight earth:150 pounds
ratio :5:7
weight neptune :7/5×150=210 pounds
If degree of variable is one then eq. is linear
so given is linear.
Answer:
The third option listed: ![\sqrt[3]{2x} -6\sqrt[3]{x}\\](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B2x%7D%20-6%5Csqrt%5B3%5D%7Bx%7D%5C%5C)
Step-by-step explanation:
We start by writing all the numerical factors inside the qubic roots in factor form (and if possible with exponent 3 so as to easily identify what can be extracted from the root):
![7\sqrt[3]{2x} -3\sqrt[3]{16x} -3\sqrt[3]{8x} =\\=7\sqrt[3]{2x} -3\sqrt[3]{2^32x} -3\sqrt[3]{2^3x} =\\=7\sqrt[3]{2x} -3*2\sqrt[3]{2x} -3*2\sqrt[3]{x}=\\=7\sqrt[3]{2x} -6\sqrt[3]{2x} -6\sqrt[3]{x}](https://tex.z-dn.net/?f=7%5Csqrt%5B3%5D%7B2x%7D%20%20-3%5Csqrt%5B3%5D%7B16x%7D%20-3%5Csqrt%5B3%5D%7B8x%7D%20%3D%5C%5C%3D7%5Csqrt%5B3%5D%7B2x%7D%20%20-3%5Csqrt%5B3%5D%7B2%5E32x%7D%20-3%5Csqrt%5B3%5D%7B2%5E3x%7D%20%3D%5C%5C%3D7%5Csqrt%5B3%5D%7B2x%7D%20%20-3%2A2%5Csqrt%5B3%5D%7B2x%7D%20-3%2A2%5Csqrt%5B3%5D%7Bx%7D%3D%5C%5C%3D7%5Csqrt%5B3%5D%7B2x%7D%20%20-6%5Csqrt%5B3%5D%7B2x%7D%20-6%5Csqrt%5B3%5D%7Bx%7D)
And now we combine all like terms (notice that the only two terms we can combine are the first two, which contain the exact same radical form:
![7\sqrt[3]{2x} -6\sqrt[3]{2x} -6\sqrt[3]{x}=\\=\sqrt[3]{2x} -6\sqrt[3]{x}](https://tex.z-dn.net/?f=7%5Csqrt%5B3%5D%7B2x%7D%20%20-6%5Csqrt%5B3%5D%7B2x%7D%20-6%5Csqrt%5B3%5D%7Bx%7D%3D%5C%5C%3D%5Csqrt%5B3%5D%7B2x%7D%20-6%5Csqrt%5B3%5D%7Bx%7D)
Therefore this is the simplified radical expression: ![\sqrt[3]{2x} -6\sqrt[3]{x}\\](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B2x%7D%20-6%5Csqrt%5B3%5D%7Bx%7D%5C%5C)
Answer:
Step-by-step explanation:
We are looking for the value of x so that the function has the given value in the following:
1) h(x) = -7x; h(x)=63
From the function given above,
If h(x) = 63, then,
h(x) = 63 = -7x
-7x = 63
Dividing the left hand side and right hand side of the equation by -7, it becomes
-7x/-7 = 63/-7
x = - 9
2) m(x) = 4x + 15; m(x)=7
From the function given above,
If m(x) = 7, then,
m(x) = 7 = 4x + 15
7 = 4x + 15
4x = 15 - 7 = 8
Dividing the left hand side and right hand side of the equation by 4, it becomes
4x/4 = 8/4
x = 2
3) q(x) = 1/2x - 3; q(x) = -4
From the function given above,
If q(x) = - 4, then,
q(x) = - 4 = 1/(2x - 3) =
Cross multiplying,
-4(2x-3) = 1
-8x +12 = 1
Collecting like terms,
-8x = 1 - 12
-8x = -11
Dividing the left hand side and right hand side of the equation by -8, it becomes
-8x/8 = -11/-8
x = 11/8